The evolution of crystalline precursors during the formation of Al-Cu-Fe quasicrystalline intermetallics in mechanically alloyed powders - Salimon, A; Korsunsky, A; Kaloshkin, S; Tcherdyntsev, V; Shelekhov, E; Sviridova, T (Trans Tech Publications, 2001)
Mechanical alloying (MA) of elemental powders in the Al-Cu-Fe system was carried out using two types of laboratory equipment (vibratory and planetary mills) to produce single phase, stable icosahedral quasicrystals. The sequence and nature of the solid state reactions during milling and subsequent annealing were studied in detail using qualitative and quantitative laboratory X-ray analysis and differential scanning calorimetry. The effect of milling parameters (energy intensity, temperature, milling time) on the course of transformations was elucidated. Specific reactions were identified which took place during annealing in different temperature ranges. The evolution of crystalline precursors of the quasicrystalline phase was established.